Determination of the predictive clinical parameters to diagnose chronic exertional compartment syndrome. Issue 2 (7th February 2018) - Fouasson-Chailloux, Alban; Menu, Pierre; Allorent, Jérémie; Dauty, Marc
Abstract: Chronic exertional compartment syndrome (CECS) is characterized by pain occurring during physical activity. As clinical examination is not sufficient to diagnose it, intracompartmental pressure (ICP) measure is used for CECS confirmation. Numerous clinical signs are reported but their diagnosis predictive ability has never been studied. We aimed to determine if the 12 classically reported clinical signs are predictive of CECS. We performed as ingle-centre retrospective cohort study on patients referred for CECS suspicion. Patients were asked to run on a treadmill. When pain occurred, post-exercise ICP was performed. We diagnosed CECS if the ICP was ≥30 mmHg and used a logistic regression to calculate the predictive value of clinical signs. One hundred twenty-five patients were evaluated. Ninety-six had CECS and 29 did not, according to the ICP 30 mmHg cut-off. Anterior and lateral compartments were the most frequently affected. After exercise, mean ICP was 58.6 mmHg ± 20.5 in the group with CECS versus 20.9 mmHg ± 4 in the group without ( p  < .001). Muscle hardness, muscle hernia after exercise, absence of pain at rest and pain recidivism for the same exercise were predictive of CECS. The predictive model associated muscle hardness (Odds Ratio (OR) = 2.18; p  < .001) and muscle hernia after exercise (OR = 1.44; p  < .001). This model identified 88.6% of CECS subjects. The ROC curve area was 0.808 [95% CI: 0.71–0.90]. This study confirmed the importance of clinical parameters to diagnose CECS. A better knowledge of the relevant parameters could help physicians to indicate invasive examinations.